De la crise de l'éducation et de ses nouveaux avatars - Alain Trouvé (Nantes Université, 2012)
We leave the diagnosis of the crisis to education while connecting her to the one who affects our contemporary societies, notably the French society. Indeed, the crisis of the education, in particular that of the school, is the product and the reflection of the more general crisis which undermines private institutions (like the family) and public (like the school) in their traditional foundations. We want to illustrate this idea at first from the new vicissitudes which still stress him from the latent contents European directives and then, from the model "neo-liberal" inspiring them. Then we underline the everlastingness of the theme of the crisis and its various characteristics (crisis of the school culture, separation of the processes of subjectivation and of rationalization, mass culture and contemporary individualism, influence exercised by "psychotechnologies" on the youth) on which seem these new vicissitudes. Finaly, reminding that the state of crisis does not result inevitably in a fatal outcome, we indicate briefly some possible openings susceptible to answer the challenges generated by the crisis